Infection-Associated Flares in Systemic Lupus Erythematosus - Giuseppe A. Ramirez; Chiara Calabrese; Marta Secci; Luca Moroni; Gabriele D. Gallina; Giovanni Benanti; Enrica P. Bozzolo; Marco Matucci-Cerinic; Lorenzo Dagna (Pathogens)
Systemic lupus erythematosus (SLE) is characterised by generalised immune dysfunction, including infection susceptibility. Infection-associated flares (IAFs) are common and might rapidly self-resolve, paralleling infection resolution, but their specific clinical phenotype is poorly understood. Therefore, we screened 2039 consecutive visits and identified 134 flares, defined as a loss of the lupus low disease activity state (LLDAS), from 1089 visits at risk spanning over multiple follow-up years, yielding an average yearly LLDAS deterioration rate of 17%. Thirty-eight IAFs were isolated from the total flares and were mostly related to bacterial and herpesvirus infections. When compared to other flares (OFs; n = 98), IAFs showed no milder patterns of organ involvement and similar rates of long-term damage accrual, as estimated by conventional clinimetrics. Arthritis in IAFs was more severe than that in OFs [median (interquartile range) DAS-28 2.6 (2.3–4.1) vs. 2.0 (1.6–2.7); p = 0.02]. Viral IAFs were characterised by atypically lower levels of anti-DNA antibodies (p < 0.001) and possibly abnormally high complement levels when compared to flares of different origin. These data suggest that IAFs are of comparable or even higher severity than OFs and may subtend distinct pathophysiological mechanisms that are poorly tackled by current treatments. Further research is needed to confirm these data.